Disease modifying actions of interleukin-6 blockade in a rat model of bone cancer pain. Issue 4 (April 2018) - Remeniuk, Bethany; King, Tamara; Sukhtankar, Devki; Nippert, Amy; Li, Nancy; Li, Fuying; Cheng, Kejun; Rice, Kenner C.; Porreca, Frank
Abstract : Abstract: Metastasis of cancer to the skeleton represents a debilitating turning point in the lives of patients. Skeletal metastasis leads to moderate to severe ongoing pain along with bone remodeling that can result in fracture, events that dramatically diminish quality of life. Interleukin-6 (IL-6) levels are elevated in patients with metastatic breast cancer and are associated with a lower survival rate. We therefore determined the consequences of inhibition of IL-6 signaling using a novel small molecule antagonist, TB-2-081, on bone integrity, tumor progression, and pain in a rodent model of breast cancer. Rat MAT B III mammary adenocarcinoma cells were injected and sealed within the tibia of female Fischer rats. Growth of these cells within the rat tibia elicited increased IL-6 levels both within the bone exudate and in the plasma, produced ongoing pain and evoked hypersensitivity, and bone fracture that was observed by approximately day 12. Systemic TB-2-081 delivered by subcutaneous osmotic minipumps starting at tumor implantation prevented tumor-induced ongoing bone pain and evoked hypersensitivity without altering tumor growth. Remarkably, TB-2-081 infusion significantly reduced osteolytic and osteoblastic bone remodeling and time to fracture likely by decreasing osteoclastogenesis and associated increase in bone resorption. These findings indicate that blockade of IL-6 signaling may represent a viable, disease-modifying strategy to prevent tumor-induced bone remodeling allowing for stabilization of bone and decreased fractures as well as diminished ongoing pain that may improve quality of life of patients with skeletal metastases. Notably, anti-IL-6 antibodies are clinically available allowing for rapid testing of these possibilities in humans. Abstract : Supplemental Digital Content is Available in the Text.Sustained administration of an interleukin-6 receptor antagonist prevented cancer-induced bone loss and pain suggesting a disease-modifying strategy for patients with cancer-induced bone pain.